(untitled) (Development Service Industry Management, 2025)
In modern conditions, a pressing issue for states is ensuring national food security, which is significantly related to the development of the agrarian sector of the national economy, providing the domestic population with economically accessible and high-quality food necessary for the vital activity of the population. Food security is one of our time’s most critical and acute global problems; some objective and subjective reasons determine its significance. When solving the problem of food security, livestock farming is a strategically important area of production that provides the necessary food resources. Development trends in the field of livestock farming have a significant impact on the effectiveness of solving these issues. The purpose of the publication is to study and assess the trends in the formation, functioning, and development of the livestock industry and its importance in ensuring the state’s food security. The article examines issues related to the features, trends in the development and functioning of the livestock industry in modern conditions. The role of livestock farming in ensuring food security is investigated. The essence of the concept of food security and the retrospective of its emergence are determined. The Global Food Security Index of Ukraine indicator in the dynamics of the indicator for 2013 - 2022 is assessed. The level of consumption of basic food products is investigated, and it is determined that the level of consumption of almost all livestock products is below the indicators of 2018 and does not ensure the country’s food security. The modern features of the development of the livestock industry and the production of basic types of livestock products are determined. The functioning of the livestock industry under martial law is investigated. Domestic food security has not been fully achieved. A significant part of the problems remains unresolved, both in terms of providing the population with necessary food products and maintaining a sufficient solvent demand for the country’s population.